2023
DOI: 10.1021/acsomega.3c04210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Desorption Damage on the Kinetic Characteristics of Coal Particle Gas Desorption

Xuan Liu,
Xiang Fu,
Bin Xiao
et al.

Abstract: There is a positive feedback mechanism of desorption, pulverization, and redesorption in the process of coal and gas outburst. The coal pore structure changes to some extent in the process of coal pulverization and has a related impact on the dynamic parameters of coal particle gas desorption. To understand the impact of desorption damage on the dynamic characteristics of coal particle gas desorption, in this paper, a self-developed coal particle gas desorption test device is used to measure the amount of meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Based on the methane diffusion coefficient at t 0 , it is found that the desorption times of four samples have a linear relationship with the diffusion coefficient (Figure ). The effect trend of desorption times on the diffusion coefficient may be due to the fact that some micropores in the coal body are opened due to damage and destruction after desorption, resulting in variations in the pores and diffusion routes of micropores and an increase in the diffusion coefficient. , In order to verify the above judgment, pore analysis of coal samples was carried out by a low-temperature liquid nitrogen adsorption experiment. Figure indicates a significant increase in pore volume peak area in coal samples after desorption, indicating the opening of micropores and pore channels during the desorption process, resulting in larger pore volume and adsorption capacity.…”
Section: Discussion Of Experimental Resultsmentioning
confidence: 99%
“…Based on the methane diffusion coefficient at t 0 , it is found that the desorption times of four samples have a linear relationship with the diffusion coefficient (Figure ). The effect trend of desorption times on the diffusion coefficient may be due to the fact that some micropores in the coal body are opened due to damage and destruction after desorption, resulting in variations in the pores and diffusion routes of micropores and an increase in the diffusion coefficient. , In order to verify the above judgment, pore analysis of coal samples was carried out by a low-temperature liquid nitrogen adsorption experiment. Figure indicates a significant increase in pore volume peak area in coal samples after desorption, indicating the opening of micropores and pore channels during the desorption process, resulting in larger pore volume and adsorption capacity.…”
Section: Discussion Of Experimental Resultsmentioning
confidence: 99%
“…The determination of diffusion coefficient is generally based on Fick 's diffusion law. Through the change curve of methane desorption amount and desorption time, ln(1- Q t / Q ∞ ) is linearly fitted with t , and then the diffusion coefficient is obtained [ 8 , 27 , 50 ].…”
Section: Pulverized Coal Driven Gas Desorption Mechanism and Theoreti...mentioning
confidence: 99%
“…The course of coal and gas outburst is also a procedure of rapid release of gas internal doublerun drill energy and coal crushing and throwing. The continuous crushing of coal body below the function of elastic potential energy accumulated in coal rock is a essential requirement for the occurrence and development of outburst [ [6] , [7] , [8] ]. Therefore, in-depth study of coal crushing related content is very important for understanding the mechanism of outburst, and it may similarly bring guiding value to assessment and prevention of coal mine disasters.…”
Section: Introductionmentioning
confidence: 99%
“…More than 95% of the raw coal is mined via underground mining methods. , The production mode of underground operations is very different from that of surface mining. There are many technical problems in underground mining, and many coal mine production accidents will be faced at the same time. Rock burst is a dynamic phenomenon in which the elastic potential energy of the surrounding coal and rock mass is suddenly and violently released under certain conditions during coal mining production, resulting in severe vibration and severe damage to the coal and rock mass, making this phenomenon very destructive. …”
Section: Introductionmentioning
confidence: 99%